Making Progress? Reproducing Hegemony Through Discourses of "Sustainable Development" in the Australian News Media. Issue 6 (18th August 2018) - Yacoumis, Paul
ABSTRACT: While numerous studies have investigated discourses of "sustainable development" in a variety of institutional and academic contexts, media discourses on this issue have remained largely unexamined. But considering the intertwined nature of media and society, the construction of sustainable development in the news may be an important factor shaping future ecological and social outcomes. Proceeding from the thesis that the news is a site in which hegemony may be reproduced, this paper critically analyses discourses used to construct sustainable development in news texts published over the 10-year period 2004–2013 across the eight most widely circulated newspapers in Australia. The findings show that sustainable development news is confined to a narrow range of discourses that largely serve to perpetuate the status quo, which is broadly consistent with the media hegemony thesis. Finally, I discuss the implications of these findings, propose possible explanations, and explore avenues for future research.